Validity and reliability of the Portuguese version of Mathematics Academic Motivation Scale (MATAMS) among third cycle of basic school students - Sousa, Sandra P. (2021)
The importance of motivation in mathematics education is expressed in the large number of studies related to the teaching and learning process. Improving students’ motivation in the mathematics classroom is a fundamental issue for teachers, investigators, and policymakers, due to its relevance in the students’ behavior and academic success. The Academic Motivation Scale is a highly applied tool to evaluate students’ motivation based on Self-Determination Theory. In Portugal, there is a lack in the analysis of the different domains of mathematics motivation defined by Self-Determination Theory, for students attending basic education. Additionally, there is no comprehensive instrument that allows that evaluation. Adapting the Academic Motivation Scale, the purpose of this study is to assess the mathematics motivation of Portuguese students who attend the third cycle of basic education. In addition, it is intended to analyze the properties of this new instrument using a sample of 349 Portuguese students aged between 12 and 17. Exploratory and confirmatory factor analysis indicated a very good validity and reliability of this measuring instrument of mathematics students’ motivation. The results of this work allow the development of educational policies that promote strategies to increase students’ motivation in mathematics.